Physical Exercise: A Novel Tool to Protect Mitochondrial Health - Sorriento, Daniela; Di Vaia, Eugenio; Iaccarino, Guido (Frontiers in Physiology, 2021)
Abstract Mitochondrial dysfunction is a crucial contributor to heart diseases. Alterations in energetic metabolism affect crucial homeostatic processes (ATP production, the generation of reactive oxygen species, and the release of pro-apoptotic factors) associated with metabolic abnormalities. In response to energetic deficiency, the cardiomyocytes activate the Mitochondrial Quality Control (MQC), a critical process in maintaining mitochondrial integrity and function. This process is compromised in cardiovascular diseases depending on the pathology's severity and represents, therefore, a potential therapeutic target. Several potential targeting molecules within this process have been identified in the last years, and therapeutic strategies have been proposed to ameliorate mitochondria monitoring and function. In this context, physical exercise is considered a non-pharmacological strategy to protect mitochondrial integrity. Physical exercise regulates MQC allowing the repair/elimination of damaged mitochondria and synthesizing new ones, thus recovering the metabolic state. In this review, we will deal with the effect of physical exercise on cardiac mitochondrial function tracing its ability to modulate specific steps in MQC both in physiologic and pathologic conditions.